Hepatocyte growth factor mimetic protects lateral line hair cells from aminoglycoside exposure - Uribe, Phillip M.; Kawas, Leen H.; Harding, Joseph W.; Coffin, Allison B. (Frontiers in Cellular Neuroscience, 2015)
Loss of sensory hair cells from exposure to certain licit drugs (e.g., aminoglycoside antibiotics, platinum-based chemotherapy agents) can result in permanent hearing loss. Here we ask if allosteric activation of the hepatocyte growth factor (HGF) cascade via Dihexa, a small molecule drug candidate, can protect hair cells from aminoglycoside toxicity. Unlike native HGF, Dihexa is chemically stable and blood-brain barrier permeable. As a synthetic HGF mimetic, it forms a functional ligand by dimerizing with endogenous HGF to activate the HGF receptor and downstream signaling cascades. To evaluate Dihexa as a potential hair cell protectant, we used the larval zebrafish lateral line, which possesses hair cells that are homologous to mammalian inner ear hair cells and show similar responses to toxins. A dose-response relationship for Dihexa protection was established using two ototoxins, neomycin and gentamicin. We found that a Dihexa concentration of 1 µM confers optimal protection from acute treatment with either ototoxin. Pretreatment with Dihexa does not affect the amount of fluorescently tagged gentamicin that enters hair cells, indicating that Dihexa’s protection is likely mediated by intracellular events and not by inhibiting aminoglycoside entry. Dihexa-mediated protection is attenuated by co-treatment with the HGF antagonist 6-AH, further evidence that HGF activation is a component of the observed protection. Additionally, Dihexa’s robust protection is partially attenuated by co-treatment with inhibitors of the downstream HGF targets Akt, TOR and MEK. Addition of an amino group to the N-terminal of Dihexa also attenuates the protective response, suggesting that even small substitutions greatly alter the specificity of Dihexa for its target. Our data suggest that Dihexa confers protection of hair cells through an HGF-mediated mechanism and that Dihexa holds clinical potential for mitigating chemical ototoxicity.